Peran Orang Tua Dalam Meningkatkan Motivasi Anak Untuk Sekolah Minggu Di Era Society 5.0 - Hesty Rolis Anabertus Rolis; Mendel Yefrichen Tabun; Elkana Yehezkiel Pasaribu; Ruth Judika Siahaan (Sekolah Tinggi Teologi Ekumene Jakarta., 2023)
Parents are people who carry out obligations which protect their children by teaching, guiding, directing, and advising them to get the child to a path that does not deviate. But in the era of society 5.0, part of people's lives is influenced by technology. This should be a concern for Christians, especially the church, teachers and parents for the spiritual growth of children. Especially the role of parents to motivate children to attend Sunday school. Sunday school can help parents recognize their children in the Lord Jesus and have strong faith growth from an early age. So the purpose of this article is to find out the problems experienced by Sunday school children and what is the role of parents in motivating their children to participate in Sunday school in the era of society 5.0. This study uses descriptive research through qualitative methods with the aim of collecting detailed, comprehensive and up-to-date data to obtain valid and truthful results. Furthermore, there are also results from this study in which parents play a role in giving children an understanding of the importance of Sunday school, taking the time to accompany their children to Sunday school, if parents do not have time to accompany Sunday school, parents can accompany children to worship online and most importantly The main thing for parents to do is to always provide motivation and example to children.